Effects of Crude Oil Imparted Sand on the Durability of Concrete (2018)
A large percentage of soils in crude oil producing areas in Nigeria were contaminated to a varying degree. Past research showed reduction in the compressive strength of concrete made with crude oil impacted sand (COIS). The current effort aimed at assessing the durability of COIS concrete. Soil samples were contaminated with crude oil concentrated levels of 0, 2.5%, 5%, 10% and 15% by weight of sand to produce COIS. Concrete design mix of 1:1.8:2.7 were made with COIS at the different concentrations from which concrete specimen – 100 mm cubes; 100 x 200 mm, and 75 x 150 mm cylinders, were made. COIS concrete were then tested for chloride and sulphate resistance using Electrical Resistivity(ER) test on 100mm x 200mm concrete cylinders and Water absorption (WA) test on 75 x 150 mm cylinders, respectively The COIS concrete was tested for Fire Resistance(FR) by testing the compressive strengths of heated 100 mm cubes. The results showed that COIS concrete exhibited an increased in durability properties as the contamination level increases. The control sample has the lowest value of ER of 119 kohm-cm which indicates low resistance to chloride ion penetration. It also has the highest value of WA of 3.9% indicating low resistance to sulphate attack. However, COIS concrete experienced reduction in strength when exposed to fire as the concentration of crude oil increases. The better durability property of the COIS concrete compliments the strength reduction.